A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam - Nguyen, Anh D.; Nguyen, Son G.; Eguchi, Katsuyuki (Zootaxa, 2021)
A new pill millipede, Rhopalomeris nagao sp. nov., is described from Vietnam. It is recognized by the following combination of characters: antennal tip with numerous sensory cones; telopods with short prefemoral and femoral trichosteles, with long, straight and acute tuberculiform femoral process, and with shorter lobuliform tibial process; syncoxial lobe being slightly concave medially, syncoxial horns being longer than lobe. A fragment of the cytochrome c oxidase subunit I (COI) gene is also provided for the new species. The K2P genetic distance of the COI between the new species and other Vietnamese glomeridans is from 10.7% to 16.9%. Two genera, Hyperglomeris and Hyleoglomeris, are considered to be non-monophyletic, but more data and samples will be needed for confirmation.